2017
DOI: 10.1027/1614-0001/a000221
|View full text |Cite
|
Sign up to set email alerts
|

The General Factor of Personality Is Stronger and More Strongly Correlated With Cognitive Ability Under Instructed Faking

Abstract: Abstract. A General Factor of Personality (GFP) can be derived by extracting one factor from a broad range of personality dimensions. Researchers are divided on whether the GFP represents social desirability or an evolved trait with survival value. The current paper tests a social desirability interpretation of the GFP by comparing one-factor models of the HEXACO under standard versus fake-good instructions (N = 185 undergraduates). Analyses include both principal components analyses (PCA) and a comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Although the field has focused considerably on common factors in recent years, the extent to which these models have theoretical utility, reflect substantive, psychologically meaningful structures, or confer additional predictive validity remains open for debate. For example, the GFP has been interpreted as a meaningful factor reflecting a continuum of positive versus negative features of personality (Musek, 2007), as well as a result of a “mistaken understanding of basic psychometrics” (Revelle & Wilt, 2013; see Hopwood, Wright, & Donnellan, 2011; MacCann, Pearce, & Jiang, 2017, for further critiques). There have also been controversies regarding the g factor of intelligence (Jensen, 1999), which has been scrutinized, given this solution’s questionable ability to account for systematic behavioral, neurological, and biological variability (e.g., see van der Maas, Dolan, Grasman, Wicherts, Huizenga, & Raijmakers, 2006).…”
mentioning
confidence: 99%
“…Although the field has focused considerably on common factors in recent years, the extent to which these models have theoretical utility, reflect substantive, psychologically meaningful structures, or confer additional predictive validity remains open for debate. For example, the GFP has been interpreted as a meaningful factor reflecting a continuum of positive versus negative features of personality (Musek, 2007), as well as a result of a “mistaken understanding of basic psychometrics” (Revelle & Wilt, 2013; see Hopwood, Wright, & Donnellan, 2011; MacCann, Pearce, & Jiang, 2017, for further critiques). There have also been controversies regarding the g factor of intelligence (Jensen, 1999), which has been scrutinized, given this solution’s questionable ability to account for systematic behavioral, neurological, and biological variability (e.g., see van der Maas, Dolan, Grasman, Wicherts, Huizenga, & Raijmakers, 2006).…”
mentioning
confidence: 99%
“…First, the relation between the GFP and cognitive abilities under low-stakes settings remains unclear ( Dunkel, Van der Linden, Beaver, & Woodley, 2014 ; Loehlin et al, 2015 ). Second, under high-stakes settings, the association between the GFP and intelligence has been found to be positive and inflated—although this relation was only found in an instructed, laboratory setting ( MacCann et al, 2017 ) and not with real job candidates ( Schermer & Goffin, 2018 ). The positive finding is consistent with the idea that intelligence is related to identifying what behavior is required in selection situations ( Bing, Whanger, Davison, & VanHook, 2004 ; Geiger, Olderbak, Sauter, & Wilhelm, 2018 ).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Yet, the authors acknowledged that this study "does not resolve the ongoing debate about whether it reflects substance or bias" (Anglim et al, 2017. p. 679); the fact that scores on a social desirability factor can be increased in selection contexts does not automatically mean that such a factor cannot have predictive value or be substantiated by other-reports (Chen, Watson, Biderman, & Ghorbani, 2016). In addition, recently a number of studies (MacCann, Pearce, & Jiang, 2017;Schermer, Holden, & Krammer, 2019;Schermer, Krammer, & Goffin, 2019) using an experimental laboratory design in which participants are instructed to fake have shown that the general factor did become more prominent under such instructions. The contrasting findings between these experimental studies and Van der Linden et al (2011) might be ascribable to the instructed nature of the former and the use of student samples; such studies have often been criticized for a lack of ecological validity (Smith & Ellingson, 2002).…”
mentioning
confidence: 99%
“…Regardless of the terminology, arguments about the cause of this factor mirror the arguments about agreement with items containing evaluative content. That is, some researchers emphasize that the general factor is substantive (Chen et al, 2016;Musek, 2007;van der Linden, Dunkel, & Petrides, 2016;van der Linden et al, 2017;Van der Linden et al, 2010) while others suggest that the general factor is caused by self-enhancement biases (Anusic et al, 2009;Bäckström, 2007;Biderman et al, 2011;MacCann, Pearce, & Jiang, 2017;Peabody & Goldberg, 1989;Pettersson et al, 2012) and methodological artefacts (Revelle & Wilt, 2013). In sum, researchers disagree over whether the general factor is mainly substantive personality or artefact.…”
Section: Social Desirability and Evaluativenessmentioning
confidence: 99%